ANALISIS IMPLEMENTASI PRINSIP BAGI HASIL, RISIKO DAN PENANGANAN PEMBIAYAAN BERMASALAH TERHADAP PEMBIAYAAN MUSYARAKAH DAN PEMBIAYAAN MUDHARABAH (STUDI KASUS:BANK SYARIAH MANDIRI KC MANADO) - Soetopo, Kartika; Saerang, David P.E.; Mawikere, Lidia (Universitas Sam Ratulangi, 2016)
The banking system in Indonesia is conducted by the dual banking system where the system is divided into conventional and Islamic. Presence of Islamic banks has providedÂ investment alternatives without worrying about the risk the development of remuneration with an uncertain interest method. But on this implementation, Islamic banking requires special treatmentÂ different from conventional banks, especially in terms of handling the risks and challenges faced by Islamic banks. The problem is how to implement the profit sharing of principal and risks and how the handling Non Performing Finance of the implementation the profit sharing. To answer the problems of research using qualitative methods by analyzing primary and secondary data so as to produce the results of interviews. The result of this study show that in musyarakah principle not much different from the mudharabah, that both a system of partnership between the two sides or more to administer a particular business with profit sharing corresponding portion (ratio) were agreed at the beginning of the agreement. On this Implementation Mudharabah and Musyarakah have a some differences. While the risk in financing the Musyarakah and mudharabah, especially on this the financing application, high relatively, among other side streaming, negligence and misconduct willful, concealment of profits by customers when customers are not honest. The amount of financing risk is shown in the ratio of non-performing finance (NPF). The high of NPF indicates the large number of borrowers who canâ€™t repay their finance in accordance with the initial agreement that has been agreed between the bank and the customer, so financing becomes problematic. Funding problems can be caused by the bank itself, the customers or external parties. Bank Syariah Mandiri (BSM) Branch Office Manado has been anticipating the event of a dispute banking, especially in the provision of financing problems. On this theory of completion financing problems, be done with several measures including the rescue action by intensive bill, rescheduling, re-requirements and realignment. Rescue actions made by bank on this condition that the customer is still considered to have good faith to settle the payment. Keywords: Islamic Banking, Profit Sharing, Risk, and Financing Problems